The participatory turn in administration: challenges in the participatory budgeting globalization - Ganuza Fernández, Ernesto; Fernández García, Manuel (Cuadernos de Trabajo Social, 2012)
Participatory budgeting is an experience born in Porto Alegre in 1989. Today, however, we find experiences in all continents. After 20 years, we can talk about over 1400 experiences spread all over the world. If we talk about the success of a project, this is one. The present work aims at contextualize this process, what it has meant and how it has taken place. The first question that arises is why a southern brazilian experience has been able to spread around the world, in context so different politically and economically. Second, we try then to understand what is participatory budgeting in the world. The aim would be to approach the participatory budgeting in such a way that it allow us to set a basis for comparing and criticizing normatively the development of these experiences and to be able to point out the singularity of participatory budgeting regarding others participatory devices.
Keywords: participatory budgeting; deliberation; inclusion; democracy from above